Penerapan Manajemen Strategi dalam Peningkatan Mutu Pendidikan di SD Nahdatul Ulama Medan - Yuli Amelia; Lukmawati Lukmawati; Putri Mulianda Hasibuan; Supardi Situmorang; Tiwi Wulandari; Mhd Syaukani Siraj; Aina Ul Mardiyah Ray (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was conducted to see how the strategic management planning carried out by the principal in improving the quality of education in schools. Whether in this strategic management planning research there is an increase in the quality of education or not. Therefore, we want to interview the principal at the Nahdatul Ulama Elementary School in Medan to get data or results from what was felt during this school.